Genetic epilepsy caused by CDKL5 gene mutations as an example of epileptic encephalopathy and developmental encephalopathy: literature review and own observations - K. Yu. Mukhin; O. A. Pylaeva; M. Yu. Bobylova; V. A. Chadaev (Русский журнал детской неврологии, 2021)
The disease caused by mutations in the CDKL5 gene (encoding cyclin-dependent kinase 5, CDK5) belongs to the group of early (infantile) epileptic encephalopathies caused by alterations in the genome. Currently, the disease is called “developmental encephalopathy and epileptic encephalopathy type 2”. This disorder is a complex combination of symptoms that develop due to deficiency or absence of the CDKL5 gene product, which is serine/threonine kinase. The CDKL5 gene is located on X chromosome; the disease has an X-linked dominant inheritance pattern. This literature review summarizes relevant studies analyzing the disease caused by CDKL5 gene mutations, including its genetic and epidemiological aspects, clinical manifestations, characteristics of epilepsy, principles of diagnosis, and therapeutic approaches. We present a case series of several patients with genetic disorders involving the CDKL5 gene.